Ecuadorian legends and folktales: a journey from storytelling to reading in the efl classroom - Martínez Sojos, Mónica Alexandra
The present paper provides insights into teaching reading to youngsters in the EFL Classroom. The analyses of a lack of reading habits along with the study of the unawareness of Cultural Identity are bond in this research. Both issues have been linked in light of teaching English as a Foreign Language with the classroom as a background. The paper shows that with adequate guidance and choice of literature the difficult task of motivating teenagers to read can be tackled. Literature related to the theme of study is explored and reviewed as to get a broader idea concerning Reading, Storytelling, Folklore and Cultural Identity. In this way, this paper centers on studying and getting depth into theories as well as on interviewing different groups of learners, with the purpose of discovering their interests towards the subject matter. Tables and figures are presented in addition to an analysis of results taking into consideration that it could be used as a pioneer contribution for further studies.